LEGAL PROTECTION OF THE BUR'AM TRADITIONAL MUSIC COMMUNITY FROM THE PERSPECTIVE OF ISLAMIC ECONOMIC LAW - Muhammad Aulia Kahfi (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
This research aims to analyse the form of dispute and settlement over the similarity of the name and quality of the Bur'am Banda Aceh Traditional Music Community, as well as the legal certainty of the Community's name rights in the perspective of haq ibtikar. Bur'am Music Community, which was first established in Banda Aceh, has become an icon of Acehnese traditional art through the use of rapai instruments. However, the name Bur'am is also used by other communities in various regions, such as Bireuen, Sabang, and Yogyakarta, raising concerns regarding the clarity of the origin and original creator of this community. The research approach used is empirical juridical with a descriptive type of analysis and data collected through interviews and documentation. The results show that name similarity disputes can be resolved through mediation by emphasising the history of the establishment and the identity of the founders. If mediation is fruitless, registration of the name Bur'am as a copyright or trademark becomes a necessary legal step to provide exclusive protection to the name. From the perspective of haq ibtikar, the name Bur'am meets the criteria of originality, creativity, and usefulness and thus deserves to be recognised as intellectual property equivalent to property in Islamic law. This recognition supports the preservation of Acehnese traditional arts and prevents potential conflicts in the future. The legal protection of the Bur'am name not only protects the rights of the creator but also ensures the authenticity and identity of Acehnese traditional art as a valuable cultural heritage.